Low temperature silver paste for HJT solar cells
By using a combination of high-content micron-scale sheet silver powder, sub-micron-scale spherical silver powder and nano-scale spherical silver powder in HJT solar cells, combined with a specific resin system, the resistivity is reduced and the printing performance is improved, and the conductivity in the prior art is solved The problem of low resistance and excellent printing performance are achieved.
Patent Information
- Application Number
- CN202310707632.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-15
- Publication Date
- 2025-01-10
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The low-temperature silver paste used in existing HJT solar cells has low conductivity, resulting in high resistivity and is difficult to take into account the printing performance of fluidity, thixotropy and aspect ratio under low resin content.
65 to 75 wt.% micron-scale flake silver powder, 17 to 17 to 17 to 17 to 17 to 17 to 17 to 18 to 19 to 19 to 19 to 19 to 19 to 19 to 19 to 19 to 19 to 19 to 19 to 19 to 19 to 19 to 19 to 19 to 19 to 19 to 19 to 19 to 19 to 19 to 19 to 19 to 19 to 19 to 19 to 19 to 19 to 19 to 19 to 19 to 19 to 19 to 19 to 19 to 19 to 19 to 19 to 19 to 19 to 19 to 19 to 19 to 19 to 19 to 19 to 19 to 19 to 19 to 1 A combination of 27 wt.% submicron spherical silver powder and 8 wt.% nano-sized spherical silver powder, combined with bisphenol S epoxy resin, modified polyurethane resin and 4,5-epoxy cyclohexane-1,2-dicarboxylic acid The resin system of diglycidyl ester resin, nano-scale spherical silver powder sintered at low temperature to form a direct connection point, reducing the resistivity.
It achieves low resistivity (3.3×10-6Ω.cm) and excellent printing performance, ensuring adhesion and aspect ratio, and improving conductivity and printing effect.
Smart Images

Figure BDA0004286464340000071
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of solar cells, and in particular to a low-temperature silver paste for HJT solar cells. Background Art
[0002] Heterojunction solar cells (HJT solar cells) are one of the new high-efficiency solar cells, with the characteristics of simple preparation process, no high-temperature sintering, high conversion efficiency, low temperature coefficient, and no light decay. At present, the maximum photoelectric conversion efficiency of large-size HJT solar cells has exceeded 25%, and there is a trend of replacing traditional PERC solar cells. The highest process temperature of silicon-based HJT solar cells during the preparation process is about 200°C, which is very different from the 900°C processing temperature of traditional crystalline silicon solar cells. Therefore, the high-temperature silver paste of traditional crystalline silicon solar energy is not suitable for HJT solar cells, and low-temperature silver paste with a curing temperature of less than 200°C should be used. Ordinary low-temperature silver paste has a solid content of 50% to 80%, and mainly uses micron-sized flaky silver powder as the conductive phase. Due to the low curing temperature, the silver powder cannot be sintered directly, and it depends on resin for bonding. Since the resin is not conductive, the resistivity of low-temperature silver paste is generally high (greater than 10 -5 Ω.cm) To reduce the resistivity of low-temperature silver paste, it is necessary to reduce the amount of resin used. However, when micron-sized flaky silver powder is used alone as the conductive functional phase, as the solid content gradually increases, when the solid content exceeds 85%, the viscosity of the silver paste exceeds 500Pa.s (0.5rpm) and the fluidity deteriorates rapidly. At the same time, in order to reduce the shading rate after silver paste printing, the silver paste is required to have a higher aspect ratio (greater than 0.35) after printing. Therefore, the low-temperature silver paste for HJT is required to have good fluidity, thixotropy, aspect ratio and other printing properties at a low resin content, while having sufficient adhesion and excellent conductive properties.
[0003] 1. In order to obtain low-resistivity low-temperature silver paste, it is necessary to increase the solid content of silver powder. According to existing research results, to obtain a resistivity less than 5*10 -6 For low-temperature silver paste with a thickness of Ω.cm, the content of silver powder should be greater than 90%. If all flaky silver powder is used, the fluidity will deteriorate due to the mutual accumulation of flaky silver powder. Spherical silver powder needs to be added to fill the pores and improve the fluidity. At the same time, the reduction of organic carrier will lead to an increase in the viscosity of the paste. It is necessary to use a resin system with low viscosity and good wettability to ensure that the viscosity of the paste is between 100 and 250 Pa.s (0.5rpm), and it has a certain thixotropy so that the aspect ratio of the 20μm wide fine grid printed by the paste is greater than 0.35. At the same time, the silver paste must have a certain adhesion after low-temperature curing. It is difficult for the existing resin system to meet the above three requirements at the same time.
[0004] 2. The main connection method of silver powder in HJT front silver paste is overlapping, relying on the overlapping between silver powders to form a conductive network for conduction. However, due to the presence of resin between silver powders, it is difficult to reduce the resistivity to 5×10 -6 Below Ω.cm, it is necessary to introduce nano silver powder that can be sintered below the silver paste curing temperature to achieve direct connection between silver powders. Summary of the invention
[0005] In view of the above technical problems, the present application provides a low-temperature silver paste for HJT solar cells, which is used to solve the problem of low conductivity in the prior art;
[0006] The present application provides a low-temperature silver paste for HJT solar cells, comprising: silver powder accounting for 92% of the total mass of the silver paste, an organic carrier accounting for 7.2% of the total mass of the silver paste, a coupling agent accounting for 0.2% of the total mass of the silver paste, a dispersant accounting for 0.3% of the total mass of the silver paste, and a curing agent accounting for 0.3% of the total mass of the silver paste;
[0007] The silver powder used is composed of 65-75wt.% of micron-grade flaky silver powder, 17-27wt.% of submicron-grade spherical silver powder, and 8wt.% of nano-grade spherical silver powder;
[0008] The organic carrier is composed of 35wt.% resin, 0.1wt.% thixotropic agent, and 64.9wt.% solvent:
[0009] The resin consists of: bisphenol S epoxy resin, modified polyurethane resin and 4,5-epoxycyclohexane-1,2-dicarboxylic acid diglycidyl ester resin;
[0010] The average particle size of the submicron spherical silver powder used is 0.2 to 0.4 μm;
[0011] The particle size of the nano-scale spherical silver powder used is controlled between 20 and 30 nm;
[0012] The particle size of the used micron-grade flaky silver powder is 3 to 6 microns.
[0013] The silver paste prepared by this formula can achieve an optimal balance in adhesion, viscosity and printing effect, avoiding the problem of reduced printing performance due to excessive viscosity, while also taking into account adhesion to achieve a reliable 5B level. The resistivity of the obtained silver paste is lower than , and because the printing performance of the obtained silver paste is good, the aspect ratio after printing is high, which can effectively improve the printing performance and adhesion ability of the existing high conductivity silver paste.
[0014] Preferably, the silver powder is composed of 70wt.% micron-grade flaky silver powder, 22wt.% submicron-grade spherical silver powder, and 8wt.% nano-grade spherical silver powder. Mixing silver powders of different morphologies in this ratio can effectively increase the number of conductive channels in the microstructure, thereby effectively improving the conductivity of the silver paste and obtaining the best conductive performance.
[0015] Preferably, the resin is composed of: bisphenol S epoxy resin accounting for 4% of the mass of the organic carrier, modified polyurethane resin accounting for 5% of the mass of the organic carrier, and 4,5-epoxycyclohexane-1,2-dicarboxylic acid diglycidyl ester resin accounting for 26% of the mass of the organic carrier. The organic carrier is prepared in this ratio, so that the silver paste can obtain the best printing performance and adhesion performance, and obtain good adhesion without increasing the viscosity, and ensure the good leveling performance and printing performance of the silver paste, and effectively improve the aspect ratio.
[0016] Preferably, the epoxy equivalent of the bisphenol S epoxy resin used is 1500-3000.
[0017] Preferably, the epoxy equivalent of the used 4,5-epoxycyclohexane-1,2-dicarboxylic acid diglycidyl ester resin is between 100 and 200. Using a resin with this equivalent can avoid excessive viscosity and improve the printing performance of the obtained silver paste.
[0018] Preferably, the thixotropic agent is hydrogenated castor oil.
[0019] Preferably, the coupling agent used is silane coupling agent KH550; and the dispersant is polyphosphate BYK110.
[0020] Preferably, the curing agent is boron trifluoride monoethylamine complex.
[0021] Preferably, the modifier used in the modified polyurethane resin is toluene diisocyanate.
[0022] Preferably, the method for preparing the silver paste comprises the following steps:
[0023] After weighing each raw material, submicron spherical silver powder and nanometer spherical silver powder are added to the organic carrier and mixed and stirred, and then micron flaky silver powder, coupling agent, dispersant, curing agent and remaining solvent are added and stirred and mixed, and then rolled to obtain conductive silver paste.
[0024] Preferably, the method for preparing the organic carrier comprises: adding the resin and the thixotropic agent into the solvent respectively, heating at 80° C. and at a rotation speed of 300 r / min, and stirring for 1 hour to obtain the organic carrier.
[0025] Preferably, the particle fineness of the conductive silver paste obtained after rolling treatment is less than 10 μm.
[0026] The silver paste prepared by this method can improve the dispersion uniformity of silver powders with different morphologies in the organic carrier, increase the number of spherical particles between flaky silver powder particles, and thus effectively improve the conductive performance.
[0027] The beneficial effects of this application include:
[0028] 1) The low-temperature silver paste for HJT solar cells provided in the present application uses flaky micron silver powder as the main conductive network, fills the gaps between the silver powders with submicron spherical silver powder and changes the overlapping structure of the flaky silver powder, thereby improving the slippage between the silver powders and the fluidity of the paste; highly dispersed and highly sintered nano-silver powder is fully dispersed between the silver powders, and forms direct connection points of the silver powders through self-sintering during solidification, thereby reducing the resistivity.
[0029] 2) The low-temperature silver paste for HJT solar cells provided in this application uses micron-sized flaky silver powder as the main conductive phase of the silver paste, and then mixes it with two auxiliary conductive silver powders, submicron-sized spherical silver powder and nano-sized spherical silver powder, to achieve the closest stacking between the silver powders and reduce the volume resistivity of the silver paste. After low-temperature sintering at 150°C to 200°C, the nano-sized spherical silver powder melts, and the silver powders of different forms mixed in this proportion can form more sintering connection points between the flaky silver powder and the spherical silver powder, further reducing the volume resistivity. The final volume resistivity is reduced to 3.3×10 -6 Ω.cm.
[0030] 3) The low-temperature silver paste for HJT solar cells provided in the present application reduces the viscosity of the organic carrier by compounding epoxy resin, polyurethane and aliphatic epoxy resin. At the same time, when the organic carrier content is low, it can also obtain better silver paste wetting performance, effectively improve the fluidity of the silver paste and thus improve the printing performance of the silver paste, so as to obtain a good aspect ratio, thereby meeting the silver paste printing performance, and at the same time, the silver paste can meet the adhesion requirements after low-temperature curing, and can pass the 3M600 100-grid test, and the adhesion is greater than 1N / mm 2 . DETAILED DESCRIPTION
[0031] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them.
[0032] The technical means that are not described in detail in this application and are not used to solve the technical problems of this application are all set according to the common knowledge in the field, and can be implemented in a variety of common knowledge settings.
[0033] Example
[0034] Unless otherwise specified, the materials and instruments used in the following examples are commercially available products.
[0035] Example 1
[0036] Silver powder accounts for 92% of the total mass of the silver paste; the silver powder is composed of 70wt.% micron-grade flaky silver powder, 22wt.% submicron-grade spherical silver powder, and 8wt.% nano-grade spherical silver powder. The average particle size of the flaky silver powder used is 3-5μm, the average particle size of the submicron-grade spherical silver powder is 0.2-0.4μm, the particle size of the micron-grade flaky silver powder used is 3-6μm; the particle size of the nano-grade spherical silver powder is controlled between 20-30nm.
[0037] The organic carrier accounts for 7.2% of the total mass of the silver paste;
[0038] The organic carrier used is composed of 35wt.% resin, 0.1wt.% thixotropic agent, and 64.9wt.% solvent:
[0039] The resin is composed of: bisphenol S epoxy resin accounting for 4% of the mass of the organic carrier, modified polyurethane resin (modifier is toluene diisocyanate) accounting for 5% of the mass of the organic carrier, and 4,5-epoxycyclohexane-1,2-dicarboxylic acid diglycidyl ester resin accounting for 26% of the mass of the organic carrier;
[0040] The epoxy equivalent of the bisphenol epoxy resin used is 1500-3000;
[0041] The epoxy equivalent of the aliphatic epoxy resin used is between 100 and 200;
[0042] The thixotropic agent is hydrogenated castor oil;
[0043] The auxiliary agent is composed of a coupling agent accounting for 0.2% of the total mass of the silver paste and a dispersant accounting for 0.3% of the total mass of the silver paste, wherein the coupling agent is a silane coupling agent KH550; and the dispersant is a polyphosphate BYK110.
[0044] The curing agent is boron trifluoride monoethylamine complex, and the added amount of the curing agent accounts for 0.3% of the total weight of the silver paste.
[0045] 1. Weigh micron-sized flaky silver powder, submicron-sized spherical silver powder, meter-sized spherical silver powder, solvent, epoxy resin, modified polyurethane, aliphatic epoxy resin, thixotropic agent, coupling agent, dispersant and latent curing agent according to the proportion;
[0046] 2. Add the weighed resin and thixotropic agent to the solvent respectively, heat to 80°C, stir at a speed of 300 r / min for 1 hour to obtain an organic carrier;
[0047] 3. Mixing and stirring the submicron spherical silver powder, the nanometer spherical silver powder and the organic carrier to obtain an auxiliary conductive silver powder pre-dispersion;
[0048] 4. Stir and mix the auxiliary conductive silver powder pre-dispersion, micron-sized flaky silver powder, coupling agent, dispersant, curing agent and remaining solvent to obtain a semi-finished silver paste;
[0049] 5. Use a three-roller rolling mill to roll the semi-finished silver paste to a fineness of less than 10 μm to obtain a finished conductive silver paste for screen printing;
[0050] 6. The finished conductive silver paste is printed on the PET film by screen printing, and printed into different shapes according to the test requirements for subsequent testing. The test sample is sintered at 180°C for 15 minutes to obtain the test sample.
[0051] Example 2
[0052] The difference from Example 1 is that: 65 wt.% of micron-level silver flakes, 27 wt.% of submicron-level silver spheres, 8 wt.% of nano-level silver spheres, and the low-temperature sintering temperature in step 6 is 150°C.
[0053] Example 3
[0054] The difference from Example 1 is that: 75 wt.% of micron-level silver flakes, 17 wt.% of submicron-level silver spheres, 8 wt.% of nano-level silver spheres, and the low-temperature sintering temperature in step 6 is 200°C.
[0055] Comparative Example 1
[0056] The difference from Example 1 is that the bisphenol epoxy resin in the organic carrier is bisphenol A epoxy resin, and the added amount is the same as that of the bisphenol S epoxy resin in Example 1.
[0057] Comparative Example 2
[0058] The difference from Example 1 is that the added resin content accounts for 45% of the total weight of the organic carrier; the added amount of bisphenol S epoxy resin accounts for 10% of the mass of the organic carrier, the added amount of modified polyurethane accounts for 9% of the mass of the organic carrier and the added amount of 4,5-epoxycyclohexane-1,2-dicarboxylic acid diglycidyl ester is 26% of the mass of the organic carrier.
[0059] Comparative Example 3
[0060] The silver powder used was pure micron-level silver flakes, and no auxiliary conductive silver powder of other morphologies was added. The rest was the same as in Example 1.
[0061] The samples obtained in Examples 1 to 3 and Comparative Examples 1 to 3 were subjected to the following tests:
[0062] 1. Adhesion rating test: Print the finished silver paste on the PET film through screen printing, and then pass the 3M600 100-grid test to obtain the adhesion rating.
[0063] 2. Volume resistivity detection: The finished silver paste is printed on the PET film through screen printing, and the square resistance of the silver film is obtained by the four-probe instrument test, and the thickness of the silver film is obtained by the film thickness meter test, and finally the volume resistivity is calculated.
[0064] 3. Printability: The silver paste of the embodiment is printed on the screen by a screen printer at the same printing speed; the line width, height and uniformity of the grid lines are checked through a 3D microscope; then the grid lines are checked under the light to see if they are full; finally, the slurry laying condition during the printing process is visually inspected.
[0065] 4. Viscosity: The viscosity of the silver paste is measured by RST rheometer.
[0066] The samples obtained in Examples 1 to 4 and Comparative Examples 1 to 2 were tested according to the above method, and the results are shown in the following table:
[0067]
[0068] It can be seen from the above table that the silver paste obtained by using the formula provided in this application can effectively take into account adhesion, adhesion and printing performance, effectively improve the printing aspect ratio, and obtain better leveling properties at a lower viscosity while ensuring adhesion, thereby effectively improving the printing effect of the obtained hardware.
[0069] In Comparative Example 1, bisphenol A epoxy resin is used instead of bisphenol S epoxy resin. Although better printing performance can be obtained, the adhesion is affected by the viscosity and cannot achieve a good effect.
[0070] In Comparative Example 2, the amount of resin used was increased. Although the adhesion was improved, the high viscosity resulted in reduced printing performance, and a good aspect ratio could not be obtained, which reduced the printing performance of the obtained silver paste.
[0071] In Comparative Example 3, only flaky silver powder was used. Although there was no surface contact, the surface contact reliability was low due to the lack of filling and adhesion of spherical silver powder, and good conductive performance could not be exerted.
[0072] Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments, or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A low-temperature silver paste for HJT solar cells, characterized in that: include: Silver powder accounting for 92% of the total mass of the silver paste, organic carrier accounting for 7.2% of the total mass of the silver paste, coupling agent accounting for 0.2% of the total mass of the silver paste, dispersant accounting for 0.3% of the total mass of the silver paste, and curing agent accounting for 0.3% of the total mass of the silver paste; The silver powder used is composed of 65-75wt.% of micron-sized flaky silver powder, 17-27wt.% of submicron-sized spherical silver powder, and 8wt.% of nano-sized spherical silver powder; The organic carrier is composed of 35 wt.% resin, 0.1 wt.% thixotropic agent, and 64.9 wt.% solvent: The resin consists of: bisphenol S epoxy resin, modified polyurethane resin and 4,5-epoxycyclohexane-1,2-dicarboxylic acid diglycidyl ester resin; The average particle size of the submicron spherical silver powder used is 0.2 to 0.4 μm; The particle size of the nano-scale spherical silver powder used is controlled between 20 and 30 nm; The particle size of the micron-sized flaky silver powder used is 3 to 6 microns; The resin consists of: bisphenol S epoxy resin accounting for 4% of the mass of the organic carrier, modified polyurethane resin accounting for 5% of the mass of the organic carrier and 4,5-epoxycyclohexane-1,2-dicarboxylic acid diglycidyl ester resin accounting for 26% of the mass of the organic carrier.
2. The low-temperature silver paste for HJT solar cells according to claim 1, characterized in that: The silver powder is composed of 70 wt.% of micron-sized flaky silver powder, 22 wt.% of submicron-sized spherical silver powder, and 8 wt.% of nano-sized spherical silver powder.
3. The low-temperature silver paste for HJT solar cells according to claim 1, characterized in that: The epoxy equivalent of the bisphenol S epoxy resin used is 1500-3000; The epoxy equivalent of the used 4,5-epoxycyclohexane-1,2-dicarboxylic acid diglycidyl ester resin is 100-200.
4. The low-temperature silver paste for HJT solar cells according to claim 1, characterized in that: The thixotropic agent is hydrogenated castor oil; the coupling agent used is silane coupling agent KH550; and the dispersant is polyphosphate BYK110.
5. The low-temperature silver paste for HJT solar cells according to claim 1, characterized in that: The curing agent is boron trifluoride monoethylamine complex.
6. The low-temperature silver paste for HJT solar cells according to claim 1, characterized in that: The modifier used in the modified polyurethane resin is toluene diisocyanate.
7. The low-temperature silver paste for HJT solar cells according to claim 1, characterized in that: The preparation method of the silver paste comprises the following steps: After weighing each raw material, submicron spherical silver powder and nanometer spherical silver powder are added to the organic carrier and mixed and stirred, and then micron flaky silver powder, coupling agent, dispersant, curing agent and remaining solvent are added and stirred and mixed, and then rolled to obtain conductive silver paste.
8. The low-temperature silver paste for HJT solar cells according to claim 7, characterized in that: The method for preparing an organic carrier comprises: adding a resin and a thixotropic agent into a solvent respectively, heating at 80° C. and a rotating speed of 300 r / min, and stirring for 1 hour to obtain an organic carrier.
9. The low-temperature silver paste for HJT solar cells according to claim 7, characterized in that: The particle size of the conductive silver paste obtained after rolling treatment is less than 10 μm.
Citation Information
Patent Citations
Low-temperature curing conductive silver paste for solar HJT fine grid and preparation method of low-temperature curing conductive silver paste
CN113707365A